Global Political Landscape In The Time Of The Covid-19 Pandemic: Realist, Liberal, And Constructivist Perspectives - Kusumawardhana, Indra (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
The vast majority of international relations scholars interpret world politics in the era of Covid-19 pandemic in accordance with realism by emphasizing on conflicts and the tendency of states to pursue their national interests. However, contemporary global politics shows complexity that cannot be understood from single perspective. This article seeks to interpret world politics in the era of Covid-19 pandemic using eclecticism approach by incorporating realism, liberalism, and constructivism. This article argues that the lanscape of global politics in the era of Covid-19 pandemic is characterized by three different features; conflicts and the pursuit of national interests, international cooperations based on the mutual benefit, and solidarity to help others dealing with the impact of Covid-19 pandemic. This finding implies that understanding international relations requires interperspective collaboration instead of debates and maintaing theoretical exclusivism.